PERILAKU COPING OLEH STREET LEVEL BUREAUCRAT PENANGANAN BENCANA COVID 19 DI KOTA BENGKULU (STUDI PADA BADAN PENANGGULANGAN BENCANA DAERAH) - Desita Rahayu; Romdana Romdana; Redho Rezki Marseven (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2022)
Street Level Bereucrats who usually handle disaster management received additional mandates as the task force for handling Covid 19 in accordance with policy of Bengkulu Mayor No. 167/2020. Having no experience in disasters pandemic and limited skills can cause problem in emergency services. This condition has caused street-level bureaucrats to do